Strategies for enhancing construction waste recycling: A usability analysis - Omer, Mazen M.; Rahimi, A. Rahman; Almutairi, Saud (MDPI, 2022)
Prior works have suggested various strategies to increase construction waste recycling (CWR) rates. However, choosing the strategies is challenging without a lateral comparison. Therefore, this study aims to compare the usability of various strategies that target the enhancement of CWR implementation. To achieve this purpose, thirteen CWR enhancement strategies were identified from a systematic literature review. Then, questionnaire survey data were collected from 106 construction project managers. The collected data were analyzed via mean score ranking, normalization, overlap analysis, agreement analysis, and factor analysis. Additionally, the data were analyzed using a proposed formula for computing usability indexes using the cost, easiness, and effectiveness values. The results show that three strategies have high usability indexes: organize temporary bins in each construction zone, identify construction activities that produce recyclable materials, and enhance company policies related to CWR. These strategies with high usability indexes are consistent with the overlapping cheap, effective, and easy strategies. This study provides researchers and practitioners with optimal strategies for enhancing CWR implementation. Effective CWR enhancement strategies can improve CWR rates in construction projects. Future researchers can also adopt this study’s approach in computing usability indexes through questionnaire surveys.